The Enhancing Corrosion Inhibition for Low Carbon Steel by Adding Graphene Oxide- WO3 in Epoxy Resin Matrix: في مصفوفة راتنجات الايبوكسيWO3-تعزيز منع التآكل للصلب منخفض الكربون عن طريق إضافة أكسيد الجرافين - ABDULFATAH HUSEEIN, WASAN; Ahmed Najem Abd; Abdulwahhab H. Majeed (ASJ - Academic Science Journal, 2024)
In this research, polyanthranilic acid, graphene oxide, and tungsten oxide nanoparticles were prepared. In the next step, GO-10%WO3, nanocomposite was prepared by adding the 10% of the weight ratio of tungsten oxide. In another step, a solution of polyanthranilic acid was mixed with epoxy resin to prepare the mother solution (Epoxy-PANA). In the last step, polymeric coatings (GO /Epoxy-PANA, GO-10%WO3/Epoxy-PANA) were prepared, in addition to (Epoxy-PANA). The prepared materials were characterized by FTIR, XRD, EDX and SEM. In the end, it’s use as anti-corrosion materials by coating it with low carbon steel. It was found that Inhibition efficiency increased by adding tungsten oxide nanoparticles to the coatings. On the other hand, the corrosion rate is reduced by adding tungsten. Moreover, it was found that adding the percentage10% of WO3 leads to affects the activation energy (Ea), enthalpy (∆H) and entropy (∆S), and this has been studied as well.